Impact of Short-Term Geomagnetic Activity on Weather and Climate Formation in Georgian Region - R. Tatishvili, Marika; M. Palavandishvili, Ana (Journals of Georgian Geophysical Society, 2020)
The investigation of possible effect of powerful magnetospheric storms on the evolution character of meteorological processes in the atmosphere aiming to identify correlation between magnetospheric disturbances and meteorological variations is presented in paper. The investigation is preconditioned by the fact, that Georgia is prone to meteorological hazards and it is especially actual to investigate their causing physical processes. Meteorological effects resulting from fluctuations in the solar wind are poorly represented in weather and climate models. Geomagnetic storm is a major disturbance of Earth's magnetosphere exchanging energy from the solar wind into the space environment surrounding Earth. These storms result from variations in the solar wind that produces major changes in the currents, plasmas, and fields in Earth’s magnetosphere. Geomagnetic indices are measure of geomagnetic activity occurring over short periods of time. They have been constructed to study the response of the Earth’s ionosphere and magnetosphere to changes in solar activity. The correlation between geomagnetic storms and meteorological elements (temperature, precipitation, wind) have been carried out for Georgian region using meteorological observation and NASA’s Solar Dynamics Observatory and NOAA Space Weather Prediction Center data. The results show that there exist dependence between weather parameters and geo-magnetic disturbances.